Peningkatan Hasil Belajar Siswa Melalui Implementasi Metode Jigsaw Berbantuan Canva Pada Pembelajaran Fikih Di Kelas VI A MI Al-Ishlah Kota Sorong - Riska Latifatul Husna; Fuad Rahmatullah; Jasman (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2024)
Low student learning outcomes result in teachers having to try to improve learning in the classroom. This study aims to improve student learning outcomes using the Jigsaw method assisted by Canva in Fikih learning in class VI A MI Al-Ishlah Kota Sorong. Based on the type, this research is a class action research (PTK). This PTK consists of two cycles, each cycle consists of four stages namely planning, implementation, observation, and reflection. In this study, researchers used data collection methods namely observation, tests, and documentation. The data analysis technique used was descriptive statistics interpreted in the form of narratives and graphs. The results showed that the use of the assisted Jigsaw method can improve student learning outcomes in class VI A MI Al-Ishlah Kota Sorong. This can be seen in the percentage of student learning outcomes in cycle I which increased from 58% to 88%. That is, there was an increase of 30% from the pre-cycle. The student learning outcomes in cycle II also experienced a significant increase, namely from 88% to 100%. That is, there was an increase of 12% from cycle I.